Homo deus as a critical category: a bioethical review of the convergence between transhumanism, posthumanism, and global progressivism - Arévalo-Pérez, Renzo Andre (2026)
The research analyzes homo deus as a manifestation of an anthropological, bioethical, and geopolitical transformation. Transhumanism and posthumanism replace divine transcendence with an instrumental dualism, conceiving the body as modifiable “hardware” and promoting a technological gnosticism. Their convergence with globalist progressivism and woke culture instrumentalizes life, denaturalizes human identity, and dismantles fundamental social structures. The Fourth Industrial Revolution, dataism, and initiatives like the Agenda 2030 reduce the individual to a “transparent dividuum” subject to biopolitical control and inequality. Bioethical resistance defends intrinsic dignity, the unity of body and soul, and awareness of finitude, guiding science toward a care-oriented paradigm, preserving freedom, ethics, and human flourishing in the face of technological dehumanization.